2015
DOI: 10.23917/biomedika.v7i2.1897
|View full text |Cite
|
Sign up to set email alerts
|

Derajad Eosinofilia Pada Penderita Infeksi Soil-Transmitted Helminth (Sth)

Abstract: ABSTRAK Soil-Transmitted Helminth (STH) menginfeksi lebih dari satu milyar orang di seluruh dunia. Di Indonesia, prevalensi STH di beberapa tempat juga masih tinggi, ada diantaranya dengan prevalensi 40-60 % pada semua umur, dengan jenis cacing dan intensitas yang berbeda-beda. Masyarakat yang tinggal di sekitar Tempat Pembuangan sampah Akhir (TPA) biasanya sanitasinya buruk. Beberapa data menunjukkan bahwa pada penderita dengan infeksi STH sering menunjukkan gejala alergi seperti gatal-gatal pada kulit dan b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
1
4
0
4
Order By: Relevance
“…Because eosinophilia not only occurs in STH infection but can occurs due to allergies, malignancy and vasculitis but there was no anamnesis in this study nor any physical examination nor a specific allergy test for atopy. The results of this study are similar to the findings in Surakarta, 21 where they were found that of 96 samples of residents living around a landfill, there was 27.1% of them who suffered from eosinophilia. However, our findings were differed from a study in Puerto Rico in densely populated and low-income areas, where they were found that eosinophilia was present in 15 out of 16 people infected with worms (94%).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Because eosinophilia not only occurs in STH infection but can occurs due to allergies, malignancy and vasculitis but there was no anamnesis in this study nor any physical examination nor a specific allergy test for atopy. The results of this study are similar to the findings in Surakarta, 21 where they were found that of 96 samples of residents living around a landfill, there was 27.1% of them who suffered from eosinophilia. However, our findings were differed from a study in Puerto Rico in densely populated and low-income areas, where they were found that eosinophilia was present in 15 out of 16 people infected with worms (94%).…”
Section: Resultssupporting
confidence: 90%
“…The results of this study were similar to the research conducted by Bestari et al which showed that the STH-uninfected subjects with normal eosinophils level are 75.3% and the STH-uninfected subjects with eosinophilia of 24.7%. 21 The results of a research which was conducted by Heukelbach et al in Brazil was showed that there were 14% of samples with eosinophilia without STH infection. 22 The finding of poor statistical association between STH infection and eosinophil level (p-value = 1.00) may be due to eosinophils level being higher in the early invasive phase than in the chronic phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enforcement of the diagnosis of infectious diseases caused by helminths carried out laboratory tests to find helminth eggs in feces. The diagnosis can also be helped by blood tests with the discovery of eosinophils (Bestar, Supargiyono, Sumarni, & Suyoko, 2015). Increased eosinophil levels can be used as a marker of soil transmitted helminth infection.…”
Section: Introductionmentioning
confidence: 99%